2009
DOI: 10.3727/096368909x471198
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of FK506, Rapamycin, and Mycophenolate Mofetil on Glucose-Stimulated Insulin Release and Apoptosis in Human Islets

Abstract: Pancreatic islet transplantation has the potential to be an effective treatment for type 1 diabetes mellitus. While recent improvements have improved 1-year outcomes, follow-up studies show a persistent loss of graft function/survival over 5 years. One possible cause of islet transplant failure is the immunosuppressant regimen required to prevent alloimmune graft rejection. Although there is evidence from separate studies, mostly in rodents and cell lines, that FK506 (tacrolimus), rapamycin (sirolimus), and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 57 publications
5
116
2
1
Order By: Relevance
“…However, upon removal of many negative or insignificant first screen factors (such as FBS, IGF-1, retinoic acid and gastrin17) from the second screen, these synergies were lost, but new synergies between nicotinamide and activin A or insulin were uncovered. While previous studies have generally shown beneficial effects of exendin-4 on beta cell function and survival [33,34], we observed a significant negative effect of exendin-4 on beta cell maturity.…”
Section: Discussioncontrasting
confidence: 94%
“…However, upon removal of many negative or insignificant first screen factors (such as FBS, IGF-1, retinoic acid and gastrin17) from the second screen, these synergies were lost, but new synergies between nicotinamide and activin A or insulin were uncovered. While previous studies have generally shown beneficial effects of exendin-4 on beta cell function and survival [33,34], we observed a significant negative effect of exendin-4 on beta cell maturity.…”
Section: Discussioncontrasting
confidence: 94%
“…We determined that media containing these factors could differentiate ADSCs into cells having a beta cell phenotype. After 30 days of differentiation, DTZ-positive clusters were observed, which were 50 -400 μm in diameter and were similar in shape to human isolated islets (Johnson et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin treatment has been shown to have mixed effects on insulin secretion, depending on the experimental conditions. [56][57][58][59] The role of mTORC1 in β-cell proliferation using rapamycin has been explored in multiple studies, which have resulted in five important observations. (1) Rapamycin treatment blocks β-cell expansion, cell size and proliferation induced by an activation of AKT in β cells.…”
Section: Proliferation Cell Size and Massmentioning
confidence: 99%